ADVANTAGES OF INDEPENDENT EDUCATION IN THE CREDIT MODULE SYSTEM IN EDUCATION - Malikova Muhabbat; Bozorova Aziza; Sayfullayeva G. I. (Web of Journals Publishing, 2023)
A credit-module system, which is the process of organizing education, is a model of assessment based on a set of Modular Technologies of teaching and a measure of credit. Carrying it in one whole is a lush and complex systemic process.
Keywords: credit-module system, education, process, way, subject, imposed, study.